A Novel Multicarrier Modulation for Integrated Sensing and Communication in Sub-THz Band - Singh D.; Kumar A.; Joshi H.D.; Singh A.K.; Sarestoniemi M.; Myllyla T.; Magarini M. (My University, 2025)
The increasing demand for joint radar and commu-nication applications has pushed both systems to use the same equipment, spectrum, and signals in millimeter (mm) and sub-THz bands. This integration improves the system's efficiency in terms of spectral usage, hardware utilization, and information processing. Motivated by this, in the present paper, a novel multicarrier modulation scheme named Generalized Adaptive Spreading Modulation (GASM) is proposed for Integrated Sensing and Communication (ISAC) in the sub-THz band. The proposed GASM-based scheme addresses various challenges of the suitable waveform for an ISAC system by spreading the symbols in both time and frequency domains with tunable spreading parameters. It is further illustrated that several current multicarrier modulation schemes like Orthogonal frequency-division multiplexing (OFDM), Fractional Fourier Transform based OFDM (FrFT-based OFDM), and Orthogonal Chirp Division Multiplexing (OCDM) are a special case of proposed GASM. The performance of the proposed GASM scheme is assessed in terms of average bit error rate (ABER) for communication; and Peak Power Loss Ratio (PPLR) and Integrated Sidelobe Level Ratio (ISLR) of Ambiguity Function (AF) for radar sensing efficiency. It is proved from simulation results that in the case of rapid time-frequency variations of the fading channel with system impairments, the proposed GASM scheme outperforms all existing Multi-carrier Schemes (MCSs) in both communication as well as sensing capabilities due to its superior capability to handle fading variations and synchronization errors. © 2024 IEEE.